Simulation of Natural Gas Pipeline Networks Based on Roughness Optimization Algorithm and Global Mesh Refinement - Yi Yang (Energy Science & Engineering)
ABSTRACT Natural gas pipeline network simulation technology is the fundamental technology of system capacity analysis, pipeline design, operation planning and optimization as well as emergency decision‐making for the whole life cycle of a given pipeline network system. There has been an increased demand for the computation efficiency and numeric accuracy of pipeline simulation with the increase of the total mileage of China's pipeline network as well as the centralize mode of one control center operating the entire system. This paper proposes a new numerical simulation method for natural gas pipeline systems based on roughness optimization and global mesh refinement. The numerical model of the natural gas pipeline system, which consists of governing equation of the pipeline fluid flow and characteristic equations of equipment, is firstly obtained by using an implicit finite difference method for discretization. The roughness identification problem is then transformed into an optimization problem by minimizing the error between measured and simulated values. The GA‐based algorithm is applied thereafter. Finally, a two‐step nonlinear iterative algorithm is proposed, which uses the coarse mesh to obtain the initial solution and the refined mesh to solve the problem to achieve accuracy and efficiency performance. The proposed method was verified by three industrial pipeline network examples. It is found that the average relative errors between the simulated and the measured data of the three cases are reduced by 3.87%, 5.06%, and 6.0%, respectively. The computational costs under 24‐h transient simulation conditions were reduced by 39%, 56%, and 65%, respectively. These numeric results show that the developed method has the advantages of stability, computation efficiency, and convergence, which provide a technical basis for the subsequent simulation of the national pipeline network.